A New Hybrid Controller for Standalone Photovoltaic Power System with Unbalanced Loads. (1st March 2020) - Pichan, Mohammad; Rastegar, Hasan
Abstract : Due to several problems such as global concern about environmental pollution, renewable energy has become an alternative source of energy. In situations such as small local loads far from the main grid, standalone hybrid power system (HPS) with inevitable unbalanced loading condition is preferred for the global grid. The four-leg inverter with a simple as well as well-performance control method is a good solution to support this condition. In this paper, with respect to the average and discretized model of the inverter, a new digital controller is proposed in the abc reference frame to control the load voltages. The proposed controller offers several advantages such as simplicity, fast dynamic response, no need for transformation among different reference frames, and full compatibility with digital implementation which makes it as an excellent option to be employed in such systems. In addition, a new hybrid controller is also proposed which not only has the advantages of the proposed digital controller but also shows superior performance under nonlinear loads without imposing a high computational burden. To verify the effectiveness of the two proposed controllers, several simulation and experimental tests under different scenarios on a 3 kW setup are performed.